Dampak Pengunaan Gadget pada Perkembangan Karakter Siswa Sekolah MI Muhammadiyah Segong (Indo-MathEdu Intellectuals Journal, 2024)
The purpose of this study is to find out how the use of student gadgets in MI Muhammdiyah Segong school, namely cellphones, has an impact on the growth of student character in MI Segong Muhammadiyah school. The type of research is qualitative descriptive, which is a research process that is carried out to analyze the information obtained in the form of words, daily behavior how to use student gadgets at MI Muhammdiyah Segong school. The data collection techniques used are observation, interviews, and documentation. The data analysis techniques used are: data reduction, data presentation, and verification. Then analyze the results of observations and interviews from the results of the research. Based on the results of the study, it was found that character formation is quite difficult to direct due to the lack of consistent supervision from parents in the use of gadgets. Children are used to giving gadgets after doing homework and when given gadgets there are no rules for when using gadgets so that children spend more time using gadgets by playing games and watching entertainment videos until they forget about educational obligations. The school in shaping the character of students is quite good in the teacher's strategy that uses methods in discussions with parents in terms of the use of gadgets for children. As well as conducting learning in the classroom to form better character values and provide positive examples to students.